Non‐uniform Photoinduced Unfolding of Supramolecular Polymers Leading to Topological Block Nanofibers. (22nd November 2021) - Tashiro, Keigo; Katayama, Kosuke; Tamaki, Kenta; Pesce, Luca; Shimizu, Nobutaka; Takagi, Hideaki; Haruki, Rie; Hollamby, Martin J.; Pavan, Giovanni M.; Yagai, Shiki
Abstract: Synthesis of one‐dimensional nanofibers with distinct topological (higher‐order structural) domains in the same main chain is one of the challenging topics in modern supramolecular polymer chemistry. Non‐uniform structural transformation of supramolecular polymer chains by external stimuli may enable preparation of such nanofibers. To demonstrate feasibility of this post‐polymerization strategy, we prepared a photoresponsive helically folded supramolecular polymers from a barbiturate monomer containing an azobenzene‐embedded rigid π‐conjugated scaffold. In contrast to previous helically folded supramolecular polymers composed of a more flexible azobenzene monomer, UV‐light induced unfolding of the newly prepared helically folded supramolecular polymers occurred nonuniformly, affording topological block copolymers consisting of folded and unfolded domains. The formation of such blocky copolymers indicates that the photoinduced unfolding of the helically folded structures initiates from relatively flexible parts such as termini or defects. Spontaneous refolding of the unfolded domains was observed after visible‐light irradiation followed by aging to restore fully folded structures. Abstract : Helically folded supramolecular polymers with a high internal rigidity undergo non‐uniform unfolding upon UV‐irradiation, affording topological block nanofibers consisting of two distinct domains with helically folded and unfolded structures.